Fabrication of gold strip thin film on glass substrate for plasmonic demodulation application - Mukhtar W.M.; Shaari S.; Menon P.S.; Razak H.A. (Institute of Electrical and Electronics Engineers Inc., 2024)
Plasmonic demodulation is a process where an optical signal due to the generation of surface plasmon polaritons (SPP) reacts with electrical domain, resulted an inverse relationship between them. In this study, fabrication processes of gold strip thin films on the glass substrates are presented. For an optimization purpose of electro-optics effect observation, the width of gold strip thin film is set as 0.5mm, which is equal to the laser beam spot diameter. First, the strip pattern is printed on a commercial transparent plastic slide. The pattern transfer process from plastic slide to glass slide is performed using UV light. Once the pattern is formed on the glass substrate, gold thin film with varies thicknesses namely 30nm, 50nm and 100nm are deposited by monitoring the sputtering time; via d.c. sputtering on the glass substrate which is partly coated with the positive photoresist. The photoresist is removed by immersing the coated glass slide in acetone solution for 15 minutes, follow with DI water for three seconds in an ultrasonic bath. This yields to the establishment of gold strip thin films with dimension of width 0.5mm length 10mm. An optimal plasmonic demodulation process is successfully acquired by using gold metal strip with thickness of 30nm and higher laser power level, namely P=1.5mW. In a conclusion, we believe that the output of this study will contribute a significant impact to the development of the plasmonic demodulator as an active device. 2015 IEEE.